The origins of the British Labour Party - Reid, J. H. Stewart, 1909-1963 (University of Minnesota Press, 1955)
What were the social and economic forces in England that gave rise to the British Labour Party? How did the party function in its formative years? How does the British labor movement compare with its American counterpart? If American labor enters politics.